Antibiotic Algae by Chemical Surface Engineering. (26th January 2018) - Kerschgens, Isabel P.; Gademann, Karl
Abstract: Chemical cell‐surface engineering is a tool for modifying and altering cellular functions. Herein, we report the introduction of an antibiotic phenotype to the green alga Chlamydomonas reinhardtii by chemically modifying its cell surface. Flow cytometry and confocal microscopy studies demonstrated that a hybrid of the antibiotic vancomycin and a 4‐hydroxyproline oligomer binds reversibly to the cell wall without affecting the viability or motility of the cells. The modified cells were used to inhibit bacterial growth of Gram‐positive Bacillus subtilis cultures. Delivery of the antibiotic from the microalgae to the bacterial cells was verified by microscopy. Our studies provide compelling evidence that 1) chemical surface engineering constitutes a useful tool for the introduction of new, previously unknown functionality, and 2) living microalgae can serve as new platforms for drug delivery. Abstract : Killer algae : Living microalgae were modified by chemical surface engineering, coating the organisms with an antibiotic hybrid to kill Gram‐positive bacteria. The antibiotic was transferred from the algae to the bacteria thereby opening new prospects for applications of microalgae in drug delivery.